(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objective: To study the clinical consequences Outcome after Arthroscopic 360 capsular release in beach Chair position for Idiopathic Adhesive Capsulitis (Frozen Shoulder) that had not been improved after any other intervention for at least 6 months. Methodology: In this study, 40 shoulders were examined in 40 participants who had adhesive capsulitis and had arthroscopic capsular release between 2018 to 2022 in Jinnah Hospital, Lahore. An ordinary Follow-up examination was were conducted at 3, 6, and 9 months after Post procedure (Follow up rate was 90 %). Preoperatively and at the follow-up exam following surgery, Range of motion and pain were assessed. Preoperatively and postoperatively, pain and Range of motion were compared using statistical analysis SPSS Version 21. Level of significance was set at p<0.05. Results: The In This study revealed that out of 40 Participants, 29 (72.5%) were females and 11 (27.5%) were males contributed in the study. The mean age was of 55.4 ± 8.6 years. Out of 40 Participants, 18 (45%) had moderate pain in their shoulders and 22 (55%) had severe pain in their shoulder. When experienced The arthroscopic release was performed in beach chair position, Active forward flexion improved from 126 ± 9.636 to 146.8 ± 8.76 degrees 9 months post operatively. The pain range improved with the mean of 7.60 ± 1.08 Pre Procedure to 2.15 ± 1.14 at 9 Months Post Operatively. Conclusion: For Patients with idiopathic adhesive capsulitis were treated in the Beach chair posture Position with arthroscopic 360° capsular release result This result in great improved functional outcomes, a significant early and long-lasting improvement in range of motion, as well as low rates of revision and complications.